A new shape of gold nanocrystals: singly twinned squashed dodecahedron - Wang, D.; Liu, Yang; You, T. (The Royal Society of Chemistry, 2010)
We demonstrate here for the first time the synthesis of squashed dodecahedron gold nanocrystals (SDGn). The SDGn is a singly twinned nanocrystal bound by {110} planes and separated by one {111} twinning plane. An atom structural model and the formation mechanism of SDGn are also proposed.